FIDELIDADE FLORAL, PLASTICIDADE COMPORTAMENTAL E FORRAGEAMENTO INDIVIDUAL DA ABELHA SEM FERRÃO Melipona (Melikerria) fasciculata SMITH, 1854 - ALMEIDA, Albeane Guimarães Silva (2022)
The efficiency of stingless bees in pollination is probably related to their dependence on floral resources from the larval to the adult stage, pollen being the protein source and nectar the carbohydrate source. These bees may exhibit floral preferences, which aim to optimize the cost-benefit of foraging. However, little is known about how individual bees specialize in collecting their resources, such as preference for certain plants, or for a specific resource. The objective of this work is to evaluate the individual foraging behavior of Melipona fasciculata, also verifying the existence of floral fidelity in relation to the distribution of resources and nutritional quality of the same. A survey of the floristic composition and the flowering phenology of plants in and around the Bacanga Campus of UFMA was conducted, verifying the influence of seasonality on the distribution of floral resources made available by bees, in the period from July 2018 to June 2019. Almost 70% of the plant species observed in the region are pollinated by bees, with floral resources distributed throughout the year. In the dry season, nectar is the most offered resource, while in the rainy season, pollen is the most available floral resource (Chapter 1). In Chapter 2, the content of total phenols and flavonoids, antioxidant activity and fatty acid composition of monofloral pollen collected by M. fasciculata in the periods from August to October 2018 (dry period) and from March to June 2019 (rainy period) were evaluated. The pollen grains of Leucaena leucocephala, Mimosa caesalpiniifolia and Mimosa pudica had the highest levels of total phenols, while Senna siamea had the highest concentrations of total flavonoids. The pollen that the bees collected from L. leucocephala showed the highest antioxidant activity. From the eight species analyzed for fatty acids, twenty-seven types of fatty acids were quantified, the most representative being α-linolenic acid, followed by linoleic acid and palmitic acid, which is important for the generation of energy for muscle contraction during the flight of the forage bees. In Chapter 3, the behavior of floral fidelity and floral source switching by marked foraging bees of M. fasciculata was verified, and whether these behaviors are related to the nutritional value (proteins and amino acids) of the pollen collected by them. In general, bees collected pollen grains with higher concentrations of proteins and amino acids more frequently. Plants of the genus Mimosa can be considered the most suitable in a diet for M. fasciculata, because they have the essential amino acids for bees, values above the minimum necessary. Some bees that switch sources during their foraging life usually switch to a source of lower quality than the initial source. For example, S. siamea, a plant with lower nutritional value than others collected, was the most used source in these exchanges, but it has special adaptations in the anthers (poricidal anthers), which restricts the collection of pollen grains to bees that vibrate the anthers, reducing interspecific competition. The collection of pollen from different sources ensures a complete diet, because a particular type of pollen can supply the nutritional deficiency of another.